100 Under $100 : One Hundred Tools for Empowering Global Women - Teutsch, Betsy Platkin (2015)
"A comprehensive look at effective low-cost, high-impact solutions that promise to empower women in the Global South, 100 under $100 explores sectors ranging from tech to public health to finance and more, offering globally attuned readers the information--and inspiration--they need to start doing their own part in helping to alleviate poverty in the developing world"--Page 4 of cover.
"A comprehensive look at effective low-cost, high-impact solutions that promise to empower women in the Global South, 100 under $100 explores sectors ranging from tech to public health to finance and more, offering globally attuned readers the information--and inspiration--they need to start doing their own part in helping to alleviate poverty in the developing world."--Page 4 of cover.
Text in English.
Keywords: Women -- Developing countries -- Economic conditions; Poor women -- Developing countries; Poverty -- Developing countries; Women in development -- Developing countries; Poor women; Poverty; Women -- Economic conditions; Women in development; Developing countries; Developing countries